Teknik Pembuatan Roll Cake Gluten Free Subtitusi Ikan Dori (John Dory L) Dengan Selai Daun Pegagan (Centella Asiatica L) - U.Yuyun Triastuti; Nisa’ul Chasanah Idris (Garina, 2022)
It is hoped that the gluten free roll cake with dori fish substitute with gotu kola leaf jam can be a snack variant that can be accepted by consumers, as well as provide sponge cake technique knowledge in making roll cake. The aims of this study were: 1) To find out the composition of the ingredients of the gluten free roll cake product, substitution of dori fish with gotu kola leaf jam. 2) Knowing the public's acceptance of gluten free roll cake substitution of dori fish with gotu kola leaf jam. The methods used in this study are library methods, experiments, hedonic tests, laboratory tests and documentation. The experimental stages in this study consisted of 2 stages, namely preliminary research and main research. The results of the study showed that the gluten-free roll cake product with the addition of 25% dory fish was the most preferred product by the panelists. The hedonic test was carried out by 35 untrained panelists who filled out a complete questionnaire. The nutritional content of gluten free roll cake with dori fish substitute with gotu kola leaf jam per 100 g is 44.68% carbohydrates, 22.08% fat, 17.22% protein, and 23.61% fiber. The technique used in making gluten free roll cake substituting dori fish with gotu kola leaf jam is the sponge cake technique. Suggestions that can be given are: 1) It is necessary to calculate the Nutrition Label Reference (ALG) for gluten free roll cake substituted for dori fish with gotu kola leaf jam 2) It is necessary to carry out a cost analysis to find out the basic cost of production and the selling price of the gluten free roll cake substituted for dori fish with gotu kola leaf jam, 3) In subsequent studies dori fish was replaced or substituted with other ingredients.